Zero-thickness interface constitutive theory for concrete self-healing effects. (1st July 2017) - Caggiano, Antonio; Etse, Guillermo; Ferrara, Liberato; Krelani, Visar
Highlights: A porosity-based model for self-healing phenomena is presented. A suitable modification of a fracture energy-based interface formulation was proposed. Continuous damage mechanics were also included. Self-healing mechanisms influenced the failure response and post-cracking softening rules. Numerical results are discussed and compared against a wide set of experimental data. Abstract: A damage-plasticity constitutive theory for zero-thickness interfaces is presented aimed at predicting time-dependent self-healing phenomena in concrete. The material model is based on fracture-energy concepts and accounts for the time evolution of concrete porosity induced by the self-healing mechanism. The accuracy and soundness of the proposed interface model are demonstrated through comparative analyses of model predictions against experimental results on three point beam tests performed up to crack opening and then, up to complete failure, before and after been subjected to different exposure conditions, respectively. A wide range of experimental tests was considered in this work for both calibration and validation purposes of the proposed interface model.